2021
DOI: 10.1007/s00068-021-01752-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of closed femoral shaft fractures in children aged 2–10 years: a systematic review and meta-analysis

Abstract: Objective To review current literature on treatment of closed femoral shaft fractures in children of 2–10 years old, with subgroup analysis of children aged 2–6 years, comparing intramedullary nailing (IMN) to conservative treatment modalities. Methods We included clinical trials and observational studies that compared traction and subsequent casting (TSC), spica casting and IMN for treatment of femur shaft fractures in children of 2–10 years of age. Subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
2
22
0
2
Order By: Relevance
“…Gordon et al reported no significant difference in fracture healing between ESIN and non-operative treatment in femur fractures, however outlines the higher impact on the family in the non-operative group due to higher need of care [ 1 ]. Van Cruchten et al suggested in their systematic review, that overall satisfaction of the parents and the patients after treatment was higher in the ESIN group [ 32 ]. Hughes et al identified impaired mobility due to spica casting of femur fracture as the main factor of family impact.…”
Section: Discussionmentioning
confidence: 99%
“…Gordon et al reported no significant difference in fracture healing between ESIN and non-operative treatment in femur fractures, however outlines the higher impact on the family in the non-operative group due to higher need of care [ 1 ]. Van Cruchten et al suggested in their systematic review, that overall satisfaction of the parents and the patients after treatment was higher in the ESIN group [ 32 ]. Hughes et al identified impaired mobility due to spica casting of femur fracture as the main factor of family impact.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis of treatment of closed femoral shaft fractures in children aged 2–10 years including 21 studies with 1,675 patients found significantly lower rates of malunion, lower means of angulation and shortening and earlier achievement of rehabilitation in children treated with ESIN compared with both immediate spica casting and traction and subsequent casting ( 11 ). Moreover, also a subgroup analysis of children aged between 2 and 6 years showed superior radiological outcomes and faster reconvalescence in the ESIN group ( 11 ). Shorter hospital stay, early mobilization and weight bearing were mentioned as additional benefits of ESIN in the literature ( 16 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immediate application of SC is often not possible without general anesthesia due to initial malalignment and in addition, the soft tissue to bone relation and muscular traction may still promote secondary displacement. Moreover, leg length discrepancy, malunion and skin breakdown are known complications ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations